Computer assisted learning in power system relaying - Lai, L.L. (IEEE transactions on education, 1995)
A computer package developed for power system protection design is used to teach protection coordination at City University, London. Examples of package use and experience gained from computer assisted learning in this subject are described. The simulation of protection systems gives students an opportunity to observe the actions of each device after they complete their protection schemes. In order to preserve flexibility within this self-learning environment, an expert system is included in the package. The use of an expert system is to make learning as effective as possible by providing guidance on the teaching material. It plays its role only if it is invoked. In other words, the expert system does not supervise learning, but can provide the necessary guidance if a request is made. If there is any error, the result of the simulation will also show the nature of the problem. The debugging function can help the students to detect the errors they have made and know how the devices work in the power system. The potential of a well-designed computer package is not only to strengthen teaching and learning, but also lead to creative contributions to the educational process. This benefit is not available through traditional lectures and textbooks.< >